Modulation of the lens water content changes the stiffness of the ex-vivo non-decapsulated bovine lenses - Qiu, Chen; Shi, Dingchang; Pan, Xingzheng; Chen, Yadi; Donaldson, Paul J. (Frontiers in Ophthalmology, 2025)
PurposeTo determine whether modulation of lens water content can alter the stiffness of the ex vivo bovine lens which have a similar stiffness profile to the presbyopic human lens.MethodsBovine lenses cultured in isotonic artificial aqueous humor (AAH) were initially subjected to either MRI imaging using a clinical 3T scanner or a spin test to obtain baseline measurements of water content and shear modulus, respectively. Lenses were then exposed to either hypotonic or hypertonic stress to swell or shrink lenses, respectively, or isotonic AAH + ouabain or high extracellular potassium (AAH-High-K+) to inhibit lens water transport, for up to 4 hours before repeating the MRI scans and spin test.ResultsIn isotonic AAH both free and total water was higher in the outer cortex of the lens relative the central lens nuclear region, but the shear modulus profile had the opposite profile being highest in the lens nucleus. Exposure to hypertonic AAH that shrinks the lens caused a loss of lens water and an increase in the shear modulus in the lens nucleus that served to steepen the shear modulus profile. In contrast, exposure to hypotonic-AAH to sweel the lens increased both free and total water content through all regions of the lens and caused a reversal of the shear modulus so that the nucleus of the lens became less stiff than the outer cortex. These effects of osmotic stress on the shear modulus profile were partially reversed upon the return of lenses to isotonic AAH. Inhibiting lens water transport under isotonic conditions caused more subtle increases in lens water content than seen with hypotonic challenge but still cause a similar softening of the nucleus but had no major effect on the shear modulus in the outer cortex of the bovine lens.ConclusionsOur results demonstrate a link between lens water content and the stiffness of the nucleus of the bovine lens. This suggests that the modulation of lens water transport represents a novel strategy for the development of pharmacological interventions designed to restore accommodation in presbyopes by softening of the nucleus of the human lens.